Insulin resistance surrogates predict hypertension plus hyperuricemia - Li, Yaxin; You, Aijun; Tomlinson, Brian; Yue, Longfei; Zhao, Kanjie; Fan, Huimin; Zheng, Liang (Journal of diabetes investigation, 2021)
Aims/Introduction To compare the association of hypertension plus hyperuricemia with four insulin resistance surrogates, including glucose and triglycerides (TyG index), TyG index with body mass index (TyG‐BMI), the ratio of triglycerides divided by high‐density lipoprotein cholesterol (TG/HDL‐C) and metabolic score for insulin resistance (METS‐IR). Materials and Methods Data from a cross‐sectional epidemiological study enrolling a representative population sample aged ≥65 years were used to calculate the four indexes. The association with hypertension plus hyperuricemia and insulin resistance surrogates was examined with multivariate logistic regression and receiver operating characteristic. Results A total of 4,352 participants were included, including 93 (2.1%) patients with hyperuricemia alone, 2,875 (66.1%) with hypertension alone and 587 (13.5%) with hypertension plus hyperuricemia. Mutivariate logistic regression showed that TyG index, TyG‐BMI, TG/HDL‐C and METS‐IR were all significantly correlated with hyperuricemia, hypertension and hypertension plus hyperuricemia. Compared with the lowest quartile, the odds ratios (OR) of the highest quartile of the four indicators for hypertension plus hyperuricemia were TyG index: OR 6.39 (95% confidence interval [CI] 4.17–9.78); TyG‐BMI: OR 8.54 (95% CI 5.58–13.09); TG/HDL‐C: OR 7.21 (95% CI 4.72–11.01); METS‐IR: OR 9.30 (95% CI 6.00–14.43), respectively. TyG‐BMI and METS‐IR had moderate discriminative abilities for hypertension plus hyperuricemia and the AUC values were 0.72 (95% CI 0.70–0.74) and 0.73 (95% CI 0.70–0.75). Conclusions The present study suggested that TyG index, TyG‐BMI, TG/HDL‐C and METS‐IR had a significant correlation with hypertension plus hyperuricemia, and TyG‐BMI and METS‐IR had discriminative abilities for hypertension plus hyperuricemia. Our study suggested that glucose and triglycerides (TyG index), TyG index with body mass index, the ratio of triglycerides divided by high‐density lipoprotein cholesterol and metabolic score for insulin resistance had a significant correlation with hypertension plus hyperuricemia, and TyG index with body mass index and metabolic score for insulin resistance had discriminative abilities for hypertension plus hyperuricemia.